TEKNIK PEMELIHARAAN LARVA IKAN KAKAP PUTIH (Lates calcarifer) DI CV. BALI AKKUA MARINE DESA MUSI KECAMATAN GEROGAK KABUPATEN BULELENG PROVINSI BALI - Halim, Atika Marisa; Widodo, Agus; Arifin, M. Zainal; Akbar, M. Baihaqi (Chanos Chanos, 2022)
Lates calcarifer is one type of Indonesian marine fish that has high economic value. Demand also continues to increase both domestically and abroad such as countries in Europe (Italy, Spain, and France). However, if it is not supported by the availability of sufficient larvae, the market demand will also not be fulfilled. The purpose of this study was to determine the technique of rearing L.calcarifer larvae and to find out the production results in CV. Bali Akkua Marine. 100.000 eggs selected from Balai Besar Riset Budidaya Laut dan Penyuluhan Perikanan, Gondol, Bali, Indonesia.The stages of egg rearing include Egg Observation (whole round eggs and floating and white in color),  acclimatization for ± 30 minutes. Eggs that have been stocked will hatch after 14-17 hours after fertilization. The optimal temperature for hatching eggs is between 27°C - 29°C. The calculation of the hatching rate (HR) obtained in the field from 100,000 eggs is 84.5%. Larvae of L. calcarifer reared reach 7-9 cm and require 63-80 days from hatching eggs. After hatching, the larvae eggs will be harvested if they reach a size of 0,6-1 cm and  SR of 75.1% . During the seed maintenance activities, the survival rate (SR) of L. calcarifer was 48.4% of the 63.500 larvae harvested.